Development of Ethnoscience-Loaded Differentiated Biology Learning Tools to Improve Critical Thinking Skills and Environmental Literacy of Phase E Students - Marwati, Utami; Paidi Paidi (International Forum of Researchers and Lecturers, 2025)
This research aims to: (1) differentiated biology learning tools with ethnoscience content, (2) determine the practicality of differentiated biology learning tools with ethnoscience content and (3) determine the effectiveness of differentiated biology learning tools with etnoscience content in improving critical thinking skills and environemantal literacy of phase E student. This study is a development research using the Design and Development Research model, which adopts the ADDIE development model comprising five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research method used is the Quasi-Experimental Design with a Nonequivalent Control Group Design approach. Data analysis includes normality tests, Levene's homogeneity test, and the Normalized Gain Score (N-Gain Score) test. The limited trial involved 30 eleventh-grade students from SMA Negeri 1 Simpangkatis. The field trial involved tenth-grade students from the same school, consisting of 31 students in the experimental class and 30 students in the control class. The data collection instruments consisted of questionnaires to gather responses from experts, teachers, and students regarding the biology learning tools, as well as tests to measure students' critical thinking skills and environmental literacy. Instrument validity was ensured through content validation by subject matter experts and media experts. The practicality of the learning tools was evaluated based on feedback from teachers and students. The results of the study showed that: (1) the developed biology learning tools were rated as highly feasible by experts; (2) the tools were considered highly practical by both teachers and students; and (3) the tools were effective in improving students' critical thinking skills and environmental literacy. This effectiveness was supported by the average gain score analysis in the experimental class, which was 0.71 for critical thinking skills (high category) and 0.57 for environmental literacy (moderate category).